Relationship Between Working Hours and Gojek Driver Income in Denpasar City - I Wayan Sugiartana; Aditya Manggala R.S.; Komang Trisna Eka Putra; Ni Made Puriati; Cokorda Istri Mas Kusumaningrat (Ekuitas: Jurnal Pendidikan Ekonomi, 2023)
The purpose of this study was to determine the working hours and income of GOJEK drivers in Denpasar, Bali, as well as the relationship between working hours and income of GOJEK drivers in Denpasar, Bali. This type of research is quantitative research using a correlative research design. The population of this study consisted of 1275 GOJEK drivers in the city of Denpasar. The sample for this study was determined using the Slovin formula which determined 304 GOJEK drivers in Denpasar City. Data collection using a questionnaire was analyzed using descriptive analysis and Pearson Product Moment correlation analysis using SPSS 24.0 for Windows. The results showed that the working time of GOJEK drivers in Denpasar Bali was 26 people (8.55%) in the high category, 178 people (58.55%) in the medium category and 100 people (32.89%) in the low category. ) very high category of 20 people (6.58%), high category of 26 people (8.55%), medium category of 154 people (50.66%), low category of 86 people (28.29%) and very low category of 18 people (5.92%), and length of service has a significant relationship with the income of GOJEK drivers in Denpasar. The city of Bali has a correlation value of 0.787 and a significance value of more than 0.000 less than Î± = 0.05.